Correlation analysis of systemic immune inflammation index with the occurrence and clinical outcomes of hypertension: a systematic review and meta-analysis - Sun, Shude; Fu, Jiamei; Yang, Jianfei; Zhao, Liang; Zhao, Boyan; Zhou, Yabin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis systematic review and meta-analysis aimed to examine the link between the systemic immune inflammation index (SII) and the incidence and clinical outcomes of hypertension (HTN).MethodsStudies on the link association SII levels with the incidence and prognosis of HTN were retrieved in PubMed, Embase, Web of Science, and Cochrane Library databases. The standardized mean difference (SMD) was employed to discuss the stability of the results and potential sources of heterogeneity. The meta-analysis was performed with Review Manager 5.4.1 and STATA 15.0 software.ResultsIn total, 19 articles were included, covering 187,195 patients. The results demonstrated that elevated SII was associated with the incidence of HTN (continuous variable: SMD = 1.22, 95% confidence interval [CI]: 0.56, 1.89, P = 0.000; categorical variable: odds ratio [OR] = 1.14, 95% CI: 1.08, 1.20, P = 0.000). Furthermore, SII was also closely linked to the prognosis of HTN patients. Subgroup analyses based on study design, sample size, region, and mean age revealed that high SII levels were associated with the incidence and prognosis of HTN. Compared to the low SII group, the incidence of HTN was greater in individuals with high SII (continuous: SMD = 1.22, 95% CI: 0.56, 1.89, P = 0.000; categorical: OR = 1.14, 95% CI: 1.08, 1.20, P = 0.000). HTN patients in the high SII group had higher rates of mortality, major cardiovascular adverse events, carotid intima-media thickness, and asymptomatic organ damage than those in the low SII group.ConclusionSII is potentially associated with the risk and prognosis of HTN, and is likely to become a valuable inflammatory marker for preventing HTN. In light of the inherent limitations of this study, more prospective, large-scale studies are necessary to confirm the findings of this study.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO CRD42024618091.